Jihad Command Movement in Pakenjeng District, Garut Regency 1976-1981 - Asep Achmad Hidayat; Usman Supendi; Ajid Thohir; Deri Sugiharto; Yan Nurcahaya (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2026)
This study examines the emergence, development, and socio-political impact of the Jihad Command movement in Pakenjeng District, Garut Regency, in the period 1976–1981. In contrast to previous research that focused more on Jihad Command at the national level, this study specifically emphasizes the local dynamics of the movement in Pakenjeng and its interaction with the community and state apparatus. This research aims to analyze the socio-political background behind the emergence of movements, the stages of movement development, organizational patterns and mobilization, and the state's response to the activities carried out. This research uses a historical-sociological approach based on the theoretical foundation of social movements and political resistance, especially related to ideological mobilization and state repression. The research method used is qualitative through document studies, archive searches, and critical analysis of relevant secondary sources. Data are analyzed through the stages of source criticism, interpretation, and historical reconstruction to obtain analytical validity and accuracy of the research context. The results of the study show that the Jihad Command movement in Pakenjeng developed through several stages, starting from the consolidation of ideology, the expansion of closed networks, to the strengthening of the narrative of religious militancy before finally experiencing setbacks due to the repressive actions of the state in the 1979-1981 period. This movement was influenced by a combination of ideological, political, and socio-economic factors, especially dissatisfaction with the New Order regime and the marginalization of certain Islamic groups. In addition, this study found that the social conditions of the local community in Pakenjeng also played a role in supporting the movement mobilization process. On the other hand, the state's response, which is characterized by surveillance, arrests, and legal action, has proven to play a major role in weakening and dissolving the movement. This research contributes to the historiographical study of radical Islamic movements in Indonesia by presenting a local perspective on Jihad Command in a broader socio-political and historical context.